Implementation of Automation System to Control Machine Voltage of Electroplating Process - Suwarno Suwarno; Calvin Chin (Universitas Medan Area, 2021)
Technology has been proliferating and it has been creating a new term in the world of technology. One of the new terms that have emerged along with technological development is The Fourth Industrial Revolution. In line with the revolution, this research has a purpose of creating a smart manufacturing concept that involves several components such as software, machines, and certain tools such as RFID. This research will be designed and developed using software development method in the form of a waterfall method and this research will use C# programming language released by American multinational technology company, which is Microsoft to create the software. This research will be assisted by several hardware devices such as RFID Reader that will serve as a tool that will read information stored in RFID Tag and RFID Tag that will be used to store information needed by system. The output of this research is a software that is capable of automating voltage adjustment of electroplating machine, monitor the voltage and ampere of the machine, and able to aid users on the electroplating process